Implementation of Cyber Counseling to Improve the Accessibility of Counseling Services - Fyarisa Fyarisa; Atasya Tara Aneldi; Afwan Syahril Manurung (Lembaga Intelektual Muda (LIM) Maluku, 2026)
In today's digital age, the need for easily accessible counseling services is increasingly urgent, especially among individuals with geographic or mobility limitations. This research aims to explore the implementation of cyber counseling as a solution to improve the accessibility of counseling services. This research identifies the challenges faced in implementing cyber counseling, including data privacy and security issues, as well as the need for training for counselors to use technology effectively. The method used was a literature review, by analyzing various academic sources, relevant articles and reports regarding cyber counseling and its impact on the accessibility of mental health services. The main source of research data is scientific articles on the database on google scholar. with a publication range of 1988 to 2024. The keywords used in the journal search were